Prospective evaluation of the lymph node proteome in dogs with multicentric lymphoma supplemented with sulforaphane - Parachini‐Winter, Cyril (J Vet Intern Med, 2020)
BACKGROUND: Lymphoma (LSA) is a common malignancy in dogs. Epigenetic changes are linked to LSA pathogenesis and poor prognosis in humans, and LSA pathogenesis in dogs. Sulforaphane (SFN), an epigenetic‐targeting compound, has recently gained interest in relation to cancer prevention and therapy. OBJECTIVE: Examine the impact of oral supplementation with SFN on the lymph node proteome of dogs with multicentric LSA. ANIMALS: Seven client‐owned dogs with multicentric LSA. METHODS: Prospective, nonrandomized, noncontrolled study in treatment‐naïve dogs with intermediate or large cell multicentric LSA. Lymph node cell aspirates were obtained before and after 7 days of oral supplementation with SFN, and analyzed via label‐free mass spectrometry, immunoblots, and Gene Set Enrichment Analysis. RESULTS: There was no clinical response and no adverse events attributed to SFN. For individual dogs, the expression of up to 650 proteins changed by at least 2‐fold (range, 2‐100) after supplementation with SFN. When all dogs where analyzed together, 14 proteins were significantly downregulated, and 10 proteins were significantly upregulated after supplementation with SFN (P < .05). Proteins and gene sets impacted by SFN were commonly involved in immunity, response to oxidative stress, gene transcription, apoptosis, protein transport, maturation and ubiquitination. CONCLUSIONS AND CLINICAL IMPORTANCE: Sulforaphane is associated with major changes in the proteome of neoplastic lymphocytes in dogs.